Diffuse interstitial lung disease: overlaps and uncertainties. - Walsh SL; Hansell DM; Walsh, Simon L F; Hansell, David M (European Radiology, 2010)
Histopathological analysis of lung biopsy material allows the diagnosis of idiopathic interstitial pneumonias; however, the strength of this diagnosis is sometimes subverted by interobserver variation and sampling. The American Thoracic Society and European Respiratory Society recommendations of 2002 provide a framework for the diagnosis of interstitial lung disease (ILD) and proposed an integrated clinical, radiological and histopathological approach. These recommendations represent a break with tradition by replacing the 'gold standard' of histopathology with the combined 'silver standards' of clinical, imaging and histopathological information. One of the pitfalls of a rigid classification system for the diagnosis of interstitial lung disease is its failure to accommodate the phenomenon of overlapping disease patterns. This article reviews the various ways that interstitial lung disease may be classified and discusses their applicability. In addition the issue of overlap disease patterns is considered in the context of histopathological interobserver variation and sampling error and how a pigeonhole approach to disease classification may overlook these hybrid entities.